Negative active material, negative electrode sheet, sodium-ion battery, and electric device
Patent Information
- Application Number
- CN202311378852.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-10-23
- Publication Date
- 2026-10-16
- Estimated Expiration
- 2043-10-23
AI Technical Summary
[0003]然而,钠离子电池在实际使用过程中面临短路、热失控等问题
[0004] This application is made in view of the above-mentioned technical problems, and its purpose is to provide a negative electrode active material, a negative electrode sheet, a sodium-ion battery and an electrical device, wherein the negative electrode active material can effectively reduce the risk of thermal runaway of sodium-ion batteries.
Smart Images

Figure CN119890243B_ABST
Abstract
Description
Technical Field
[0001] This application relates to the field of batteries, and more specifically, to a negative electrode active material, a negative electrode sheet, a sodium-ion battery, and an electrical device. Background Technology
[0002] Compared to lithium-ion batteries, sodium-ion batteries have the advantages of lower cost and abundant sodium resources, making them a viable alternative and showing great application potential in markets such as large-scale energy storage and passenger vehicles. Hard carbon, with its lower operating voltage and good cycle stability, is considered the most promising anode material for sodium-ion batteries.
[0003] However, sodium-ion batteries face problems such as short circuits and thermal runaway in practical use. When short circuits or thermal runaway occur, hard carbon, due to its sodium storage mechanism, forms a large amount of metalloid sodium during battery cycling. In the event of thermal runaway, this rapidly exacerbates the problem, potentially leading to fires or explosions in sodium-ion batteries. Therefore, improving the thermal runaway problem of sodium-ion batteries has become an urgent technical challenge. Summary of the Invention
[0004] This application is made in view of the above-mentioned technical problems, and its purpose is to provide a negative electrode active material, a negative electrode sheet, a sodium-ion battery and an electrical device, wherein the negative electrode active material can effectively reduce the risk of thermal runaway of sodium-ion batteries.
[0005] In a first aspect, a negative electrode active material is provided, comprising: hard carbon, wherein the true density ρ of the hard carbon satisfies: 1.3 g / cm³. 3 ≤ρ≤2.0g / cm 3 ; a convertible sodium storage material, wherein the convertible sodium storage material is capable of forming a compound with sodium.
[0006] In the embodiments of this application, the negative electrode active material contains materials with a true density of 1.3 g / cm³. 3 -2.0g / cm 3 Hard carbon conversion-type sodium storage materials within the specified range, with a true density within this range, can provide higher capacity for sodium-ion batteries. These conversion-type materials allow sodium ions to intercalate and form compounds, thus storing sodium. This reduces the formation of metalloid sodium during battery cycling, helping to lower the risk of thermal runaway in sodium-ion batteries. Furthermore, sodium compounds typically have high melting points, preventing rapid propagation of thermal runaway in the event of a runaway, further improving the safety performance of sodium-ion batteries.
[0007] In one possible implementation, the mass content m1 of hard carbon in the negative electrode active material satisfies: 80% ≤ m1 ≤ 99%; optionally, 85% ≤ m1 ≤ 98%.
[0008] In one possible implementation, the mass content m2 of the convertible sodium storage material in the negative electrode active material satisfies: 1% ≤ m2 ≤ 20%; optionally, 2% ≤ m2 ≤ 15%.
[0009] In the embodiments of this application, by controlling the mass content of hard carbon and conversion-type sodium storage materials in the negative electrode active material, the capacity and sodium storage mechanism of the negative electrode active material can be effectively controlled, and the formation of metalloid sodium can be reduced. Thus, when the negative electrode active material is applied to sodium-ion batteries, the sodium-ion batteries can have both high capacity and good safety.
[0010] In one possible implementation, the conversion-type sodium storage material includes at least one of alloy-type sodium storage materials, metal oxide sodium storage materials, metal sulfide sodium storage materials, metal selenide sodium storage materials, and metal phosphide sodium storage materials.
[0011] In one possible implementation, the alloy-type sodium storage material includes at least one of Sn, Ge, Pb, P, Sb, Bi, Si, and their alloys.
[0012] In one possible embodiment, the metal oxide sodium storage material includes at least one of the following: oxides of Sn, Ge, Pb, P, Sb, Bi, and Si.
[0013] In one possible implementation, the metal sulfide sodium storage material includes at least one of the following: Sn sulfide, Ge sulfide, Pb sulfide, P sulfide, Sb sulfide, Bi sulfide, and Si sulfide.
[0014] In one possible implementation, the metal selenide sodium storage material includes at least one of the following: Sn selenide, Ge selenide, Pb selenide, P selenide, Sb selenide, Bi selenide, and Si selenide.
[0015] In one possible implementation, the metal phosphide sodium storage material includes at least one of the following: Sn phosphide, Ge phosphide, Pb phosphide, Sb phosphide, Bi phosphide, and Si phosphide.
[0016] In one possible implementation, the compound formed by the conversion-type sodium storage material and sodium includes at least one of the following: sodium alloy, sodium oxide, sodium sulfide, sodium selenide, and sodium phosphide.
[0017] In one possible implementation, the average volumetric particle size distribution Dv50 of the convertible sodium storage material satisfies: 3.5μm≤Dv50≤6.5μm; optionally, 4μm≤Dv50≤6μm.
[0018] In one possible implementation, the specific surface area BET of the conversion-type sodium storage material satisfies: 3m² 2 / g≤BET≤15m 2 / g; optionally, 4m 2 / g≤BET≤10m 2 / g.
[0019] In one possible implementation, the compaction density α of the negative electrode active material under a pressure of 3T satisfies: 0.85 g / cm³. 3 ≤α≤1.6g / cm 3 Optionally, 0.88 g / cm³ 3 ≤α≤1.5g / cm 3 .
[0020] In one possible implementation, the specific capacity W1 of the hard carbon satisfies: 150mAh / g≤W1≤350mAh / g; optionally, 280≤W1≤350mAh / g.
[0021] In one possible implementation, the discharge capacity W2 of the conversion sodium storage material satisfies: 300mAh / g≤W2≤2000mAh / g; optionally, 300mAh / g≤W2≤1500mAh / g.
[0022] In a second aspect, a negative electrode sheet is provided, the negative electrode sheet comprising the negative electrode active material in any of the embodiments of the first aspect.
[0023] Thirdly, a sodium-ion battery is provided, the sodium-ion battery including the negative electrode sheet in any of the embodiments of the second aspect.
[0024] Fourthly, an electrical device is provided, the electrical device comprising a sodium-ion battery as described in any of the embodiments of the third aspect. Attached Figure Description
[0025] To more clearly illustrate the technical solutions of the embodiments of this application, the drawings used in the embodiments of this application will be briefly introduced below. Obviously, the drawings described below are only some embodiments of this application. For those skilled in the art, other drawings can be obtained based on the drawings without creative effort.
[0026] Figure 1 This is a schematic diagram of a sodium-ion battery cell according to an embodiment of this application.
[0027] Figure 2 This is a schematic diagram of a sodium-ion battery module according to an embodiment of this application.
[0028] Figure 3This is a schematic diagram of a sodium-ion battery according to an embodiment of this application.
[0029] Figure 4 This is another schematic diagram of a sodium-ion battery according to an embodiment of this application. Detailed Implementation
[0030] The following detailed description, with appropriate reference to the accompanying drawings, specifically discloses embodiments of the negative electrode active material, negative electrode sheet, sodium-ion battery, and power-consuming device of this application. However, unnecessary detailed descriptions may be omitted. For example, detailed descriptions of well-known matters and repetitive descriptions of practically identical structures may be omitted. This is to avoid unnecessarily lengthy descriptions and to facilitate understanding by those skilled in the art. Furthermore, the accompanying drawings and the following description are provided for the purpose of enabling those skilled in the art to fully understand this application and are not intended to limit the subject matter of the claims.
[0031] The "range" disclosed in this application is defined by a lower limit and an upper limit. A given range is defined by selecting a lower limit and an upper limit, which define the boundaries of a particular range. Ranges defined in this way can include or exclude endpoints and can be arbitrarily combined; that is, any lower limit can be combined with any upper limit to form a range. For example, if ranges of 60-120 and 80-110 are listed for a specific parameter, it is expected that ranges of 60-110 and 80-120 are also included. Furthermore, if minimum range values of 1 and 2 are listed, and if maximum range values of 3, 4, and 5 are listed, then the following ranges are all expected: 1-3, 1-4, 1-5, 2-3, 2-4, and 2-5. In this application, unless otherwise stated, the numerical range "ab" represents a shortened representation of any combination of real numbers between a and b, where a and b are real numbers. For example, the numerical range "0-5" indicates that all real numbers between "0-5" have been listed in this article; "0-5" is simply a shortened representation of these numerical combinations. Furthermore, when a parameter is stated as an integer ≥2, it is equivalent to disclosing that the parameter is, for example, an integer such as 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, etc.
[0032] In the description of this application, it should be noted that, unless otherwise stated, "a plurality of" means two or more; the terms "upper," "lower," "left," "right," "inner," "outer," etc., indicating orientation or positional relationships are only for the convenience of describing this application and simplifying the description, and do not indicate or imply that the device or element referred to must have a specific orientation, or be constructed and operated in a specific orientation, and therefore should not be construed as a limitation on this application. Furthermore, the terms "first," "second," "third," etc., are used for descriptive purposes only and should not be construed as indicating or implying relative importance.
[0033] Unless otherwise specified, all steps in this application may be performed sequentially or randomly, preferably sequentially. For example, the method includes steps (a) and (b), indicating that the method may include steps (a) and (b) performed sequentially, or it may include steps (b) and (a) performed sequentially. For example, the mention that the method may also include step (c) indicates that step (c) may be added to the method in any order. For example, the method may include steps (a), (b), and (c), or it may include steps (a), (c), and (b), or it may include steps (c), (a), and (b), etc.
[0034] Unless otherwise specified, all embodiments and optional embodiments of this application can be combined to form new technical solutions.
[0035] Unless otherwise specified, all technical features and optional technical features of this application may be combined to form new technical solutions.
[0036] Unless otherwise specified, the following terms have the following meanings. Any undefined terms have their technically accepted meanings.
[0037] If mentioned, "hard carbon" refers to disordered carbon materials that cannot form a regular graphite structure at temperatures above 3000℃. Its precursors are generally polymers with multiple heteroatoms, such as sugars, cellulose, and phenolic resins.
[0038] If mentioned, "true density" refers to the actual mass of a solid substance per unit volume in an absolutely dense state, that is, the density after removing internal pores or voids between particles.
[0039] If mentioned, "conversion-type sodium storage materials" refer to materials in which sodium ions can be embedded and react chemically to form compounds, such as metals, alloys, metal oxides, metal sulfides, metal tin compounds, etc.
[0040] As mentioned, "alloy-type sodium storage materials" refer to materials that can form alloys with sodium. In electrochemical reactions, sodium storage is based on alloying and dealloying with sodium. Examples include Sn, Sb, Pb, Ge, and P.
[0041] As mentioned, "sodium-storing metal oxide materials" refer to metal oxides that allow sodium ions to be embedded within them and react with sodium ions to form sodium oxides, storing sodium based on a conversion reaction with sodium. Examples include NiCo2O4, Sb2O3, Co3O4, Fe3O4, Fe2O3, SnO, and SnO2.
[0042] As mentioned, "metal sulfide sodium storage materials" refer to metal sulfides that allow sodium ions to intercalate and form sodium sulfides. They store sodium based on a conversion reaction with sodium. Examples include FeS, SnS2, CoS, Ni2S3, MoS2, ZnS, and TiS2.
[0043] If mentioned, the "discharge curve" refers to the graph showing the relationship between the electrode potential and the battery capacity during the discharge process when a certain material is used as the electrode active material.
[0044] Typically, a battery cell includes a positive electrode, a negative electrode, an electrolyte, and a separator. During the charging and discharging process, active ions move back and forth between the positive and negative electrodes, inserting and extracting. The electrolyte acts as a conductor between the positive and negative electrodes. The separator, located between the positive and negative electrodes, primarily prevents short circuits while allowing active ions to pass through. In some embodiments, this battery cell is also referred to as a secondary battery.
[0045] During the charging process of a sodium-ion battery, sodium ions are released from the positive electrode active material, move and embed into the negative electrode material; while during the discharging process, sodium ions are released from the negative electrode material, move and embed into the positive electrode active material.
[0046] It should be understood that the “intercalation” process described in this application refers to the process by which sodium ions are intercalated in the positive electrode active material and the negative electrode material due to an electrochemical reaction, and the “deintercalation” and “deintercalation” processes described in this application refer to the process by which sodium ions are deintercalated in the positive electrode active material and the negative electrode material due to an electrochemical reaction.
[0047] With the in-depth research and application of sodium-ion batteries, new requirements have been put forward for their capacity and safety performance. For example, in some application scenarios (such as electric vehicles and other electrical devices), once a short circuit occurs, the internal temperature of the battery will rise rapidly and lead to thermal runaway, which is not conducive to the user of the electrical device reacting to it. Moreover, for sodium-ion batteries, hard carbon is usually used as the negative electrode active material. At present, the process of storing sodium in sodium-ion batteries with hard carbon is generally considered to have three mechanisms: (1) the adsorption mechanism of sodium ions at the edge defects and surface open pores of the graphite-like layer; (2) the intercalation and deintercalation mechanism of sodium ions between the graphite-like layers; and (3) the pore-filling mechanism of sodium ions depositing in the closed pores and some open pores of hard carbon to form metallic sodium. Among them, the pore-filling mechanism is considered to be the main mechanism contributing to the capacity of sodium-ion batteries. That is to say, the higher the capacity of the sodium-ion battery, the more metallic sodium is formed during the charging and discharging process of the battery. Based on this, in the aforementioned application scenarios, once a short circuit occurs in the battery, sodium-ion batteries using hard carbon as the negative electrode active material are more prone to thermal runaway because the thermal reaction temperature of hard carbon itself is lower than that of graphite and there is a large amount of metalloid sodium. Once thermal runaway occurs, the heat spreads rapidly, and in severe cases, it can cause thermal runaway of the entire sodium-ion battery, seriously affecting the safety of the sodium-ion battery.
[0048] In view of this, this application provides a negative electrode active material, a negative electrode sheet, a sodium-ion battery, and an electrical device. In addition to hard carbon, the negative electrode active material also includes a conversion-type sodium storage material, which can regulate the sodium storage mechanism of the negative electrode active material and effectively reduce the risk of sodium ion thermal runaway.
[0049] First, embodiments of this application provide a negative electrode active material, including hard carbon and a conversion-type sodium storage material capable of forming a compound with sodium. The true density ρ of the hard carbon satisfies: 1.3 g / cm³. 3 ≤ρ≤2.0g / cm 3 .
[0050] Specifically, ρ can be 1.3 g / cm³. 3 1.4g / cm 3 1.5g / cm 3 1.6g / cm 3 1.7g / cm 3 1.8g / cm 3 , or its value is within the range obtained by combining any two of the above values.
[0051] Conversion-type sodium storage materials primarily utilize an intercalation mechanism to store sodium, allowing sodium ions to intercalate and react chemically to form sodium compounds. Hard carbon, on the other hand, primarily uses a pore-filling mechanism, forming metalloid sodium during the storage process. Hard carbon itself has a low thermal reaction temperature, resulting in a higher risk of thermal runaway. Furthermore, the metalloid sodium formed during hard carbon storage has a low melting point, which would rapidly worsen thermal runaway conditions. Sodium compounds, however, have a high melting point, and the temperature at which sodium-ion batteries experience thermal runaway typically does not reach their melting point. Therefore, for negative electrode active materials, introducing conversion-type sodium storage materials can effectively reduce the formation of metalloid sodium, lower the risk of thermal runaway in sodium-ion batteries, and help slow the rate of heat propagation in the event of runaway. This improves the safety of sodium-ion batteries, especially in passenger vehicle applications, where it can buy passengers valuable escape time.
[0052] In one embodiment, the mass content m1 of hard carbon in the negative electrode active material satisfies: 80% ≤ m1 ≤ 99%; optionally, 85% ≤ m1 ≤ 98%.
[0053] Specifically, m1 can be 80%, 80.5%, 81%, 81.5%, 82%, 82.5%, 83%, 83.5%, 84%, 84.5%, 85%, 85.5%, 86%, 86.5%, 87%, 87.5%, 88%, 88.5%, 89%, 89.5%, 90%, 90.5%, 91%, 91.5%, 92%, 92.5%, 93%, 93.5%, 94%, 94.5%, 95%, 95.5%, 96%, 96.5%, 97%, 97.5%, 98%, 98.5%, 99%, or a value within the range obtained by any combination of the above two values.
[0054] Hard carbon has a high reversible capacity, and it can be selected as the main material in the negative electrode active material. Controlling its mass content within a high range helps to improve the specific capacity of the negative electrode active material.
[0055] In one embodiment, the mass content m2 of the conversion-type sodium storage material in the negative electrode active material satisfies: 1% ≤ m2 ≤ 20%; optionally, 2% ≤ m2 ≤ 15%.
[0056] Specifically, m2 can be 1%, 1.5%, 2%, 2.5%, 3%, 3.5%, 4%, 4.5%, 5%, 5.5%, 6%, 6.5%, 7%, 7.5%, 8%, 8.5%, 9%, 9.5%, 10%, 10.5%, 11%, 11.5%, 12%, 12.5%, 13%, 13.5%, 14%, 14.5%, 15%, 15.5%, 16%, 16.5%, 17%, 17.5%, 18%, 18.5%, 19%, 19.5%, 20%, or a value within the range obtained by any combination of the above two values.
[0057] Conversion-type sodium storage materials also possess high capacity and good safety performance, but their cycle stability is inferior to that of hard carbon. Therefore, by controlling the mass content of conversion-type sodium storage materials within an appropriate range, the safety of the negative electrode active material can be improved while simultaneously ensuring good cycle performance.
[0058] In the embodiments of this application, by adjusting the proportion of hard carbon and conversion-type sodium storage material in the negative electrode active material, the sodium storage mechanism of the negative electrode active material can be controlled, the contribution of the intercalation-type sodium storage material based on the intercalation mechanism to the capacity of the sodium-ion battery can be increased, the generation of metalloid sodium can be reduced, and the possibility of thermal runaway of the sodium-ion battery can be reduced.
[0059] In one embodiment, the conversion-type sodium storage material includes at least one of alloy-type sodium storage materials, metal oxide sodium storage materials, metal sulfide sodium storage materials, metal selenide sodium storage materials, and metal phosphide sodium storage materials.
[0060] In one embodiment, the alloy-type sodium storage material includes at least one of Sn, Ge, Pb, P, Sb, Bi, Si, and their alloys.
[0061] Sodium alloy storage materials typically possess high capacity, but when used alone as active materials for sodium storage, their significant volume expansion rate negatively impacts the reversible capacity and cycle stability of sodium-ion batteries. Sodium can react with sodium alloy storage materials to form alloy compounds, namely sodium-metal alloys. The melting point of sodium-metal alloys is much higher than that of metallic sodium. Therefore, by introducing sodium alloy storage materials into the negative electrode active material, the risk of thermal runaway in sodium-ion batteries can be reduced, and in the event of thermal runaway, the rate of heat propagation can be slowed, effectively improving the safety performance of sodium-ion batteries.
[0062] It should be understood that if a metal exists in many different crystal forms, the above chemical formula can represent the metal including its different crystal forms.
[0063] In one embodiment, the metal oxide sodium storage material includes at least one of the following: oxides of Sn, Ge, Pb, P, Sb, Bi, and Si.
[0064] In one embodiment, the metal sulfide sodium storage material includes at least one of the following: Sn sulfide, Ge sulfide, Pb sulfide, P sulfide, Sb sulfide, Bi sulfide, and Si sulfide.
[0065] In one embodiment, the metal selenide sodium storage material includes at least one of the following: Sn selenide, Ge selenide, Pb selenide, P selenide, Sb selenide, Bi selenide, and Si selenide.
[0066] In one embodiment, the metal phosphide sodium storage material includes at least one of Sn phosphide, Ge phosphide, Pb phosphide, Sb phosphide, Bi phosphide, and Si phosphide.
[0067] The principle of sodium storage using metal oxides, sulfides, selenides, and phosphides is based on multi-electron conversion reactions with sodium, and they also have high capacity. However, when used alone as negative electrode active materials, their cycle performance is unstable. Sodium can react with metal oxides, metal sulfides, metal selenides, and metal phosphides to form compounds, such as sodium oxides, sodium sulfides, sodium selenides, and sodium phosphides. Sodium compounds have melting points much higher than those of metallic sodium. Therefore, by introducing metal oxides, metal sulfides, metal selenides, and metal phosphides into negative electrode active materials with hard carbon as the main material, the risk of thermal runaway in sodium-ion batteries can be reduced, and in the event of thermal runaway, the rate of heat propagation can be slowed down, effectively improving the safety performance of sodium-ion batteries.
[0068] In one embodiment, the compound formed by the conversion sodium storage material and sodium includes at least one of the following: sodium alloy, sodium oxide, sodium sulfide, sodium selenide, and sodium phosphide.
[0069] In one embodiment, the average volumetric particle size Dv50 of the convertible sodium storage material satisfies: 5 μm ≤ Dv502 ≤ 30 μm; optionally, 5 μm ≤ Dv502 ≤ 25 μm. Specifically, the average volumetric particle size Dv502 of the convertible sodium storage material can be: 5 μm, 7 μm, 9 μm, 10 μm, 12 μm, 14 μm, 16 μm, 18 μm, 20 μm, 22 μm, 24 μm, 25 μm, 26 μm, 28 μm, 30 μm, or a value within the range obtained by any combination of the above two values.
[0070] In the embodiments of this application, controlling the average volumetric particle size of hard carbon within a suitable range helps to reduce battery polarization and improve the cycle performance of sodium-ion batteries.
[0071] In one embodiment, the average volumetric particle size Dv50 of the hard carbon material satisfies: 3.5 μm ≤ Dv501 ≤ 6.5 μm; optionally, 4 μm ≤ Dv501 ≤ 6 μm. Specifically, the average volumetric particle size Dv501 of the hard carbon can be 3.5 μm, 4 μm, 4.5 μm, 5 μm, 5.5 μm, 6 μm, 6.5 μm, or a value within the range obtained by any combination of the above two values. It should be understood that the subscripts "1" and "2" in "Dv501" and "Dv502" are only used for distinction and are set to avoid confusion regarding the average volumetric particle size of conversion materials or hard carbon, and do not cause any other limitations.
[0072] In the embodiments of this application, by controlling the average volume particle size of the conversion sodium storage material in the negative electrode active material within a suitable range, it is beneficial for the insertion and extraction of sodium ions when applied to sodium-ion batteries, so that the capacity of the negative electrode active material can be fully released, thereby helping to improve the energy density of sodium-ion batteries.
[0073] In one embodiment, the specific surface area BET of the conversion sodium storage material satisfies: 3m² 2 / g≤BET≤15m 2 / g; optionally, 4m 2 / g≤BET≤10m 2 / g.
[0074] Specifically, the specific surface area BET of the conversion sodium storage material can be: 3m² 2 / g、4m 2 / g、5m 2 / g、6m 2 / g、7m 2 / g、8m 2 / g、9m 2 / g, 10m 2 / g、11m 2 / g、12m 2 / g、13m 2 / g、14m 2 / g, 15m 2 / g, or its value range is within the range obtained by any combination of the above two values.
[0075] In one embodiment, the compaction density α of the negative electrode active material under a pressure of 3T satisfies: 0.85 g / cm³. 3 ≤α≤1.6g / cm 3 Optionally, 0.88 g / cm³3 ≤α≤1.5g / cm 3 .
[0076] Specifically, α can be 0.85 g / cm³. 3 0.88g / cm 3 0.9g / cm 3 0.92g / cm 3 0.94g / cm 3 0.96g / cm 3 0.98g / cm 3 1.0g / cm 3 1.1g / cm 3 1.2g / cm 3 1.3g / cm 3 1.4g / cm 3 1.5g / cm 3 1.6g / cm 3 , or its value range is within the range obtained by any combination of the above two values.
[0077] In one embodiment, the specific capacity W1 of the hard carbon satisfies: 150mAh / g≤W1≤350mAh / g; optionally, 280mAh / g≤W1≤350mAh / g.
[0078] Specifically, W1 can be 150mAh / g, 180mAh / g, 200mAh / g, 220mAh / g, 240mAh / g, 260mAh / g, 280mAh / g, 300mAh / g, 320mAh / g, 340mAh / g, 350mAh / g, or a value within the range obtained by any combination of the above two values.
[0079] In one embodiment, the specific capacity W2 of the conversion sodium storage material is satisfied with: 300mAh / g≤W2≤2000mAh / g; optionally, 300mAh / g≤W2≤1500mAh / g.
[0080] Specifically, W2 can be 300mAh / g, 400mAh / g, 500mAh / g, 600mAh / g, 700mAh / g, 800mAh / g, 900mAh / g, 1000mAh / g, 1100mAh / g, 1200mAh / g, 1300mAh / g, 1400mAh / g, 1500mAh / g, 1600mAh / g, 1700mAh / g, 1800mAh / g, 1900mAh / g, 2000mAh / g, or a value within the range obtained by any combination of the above two values.
[0081] The negative electrode active materials provided in this application include hard carbon and conversion-type sodium storage materials, both of which have high specific capacity. The negative electrode active material obtained by combining the two also has high specific capacity and can be applied to high-capacity, high-energy-density sodium-ion batteries.
[0082] Next, we will provide a detailed introduction to the electrode materials, positive electrode, negative electrode, separator, and electrolyte in sodium-ion batteries.
[0083] [Negative electrode plate]
[0084] A negative electrode typically includes a negative current collector, or includes a negative current collector and a negative electrode film layer disposed on at least one surface of the negative current collector, the negative electrode film layer including a negative electrode active material.
[0085] As an example, the negative electrode current collector has two surfaces opposite each other in its own thickness direction, and the negative electrode film layer can be disposed on either or both of the two opposite surfaces of the negative electrode current collector.
[0086] Optionally, the negative electrode current collector can be a metal foil or a composite current collector. For example, copper foil can be used as the metal foil. The composite current collector may include a polymer material substrate and a metal layer formed on at least one surface of the polymer material substrate. The composite current collector can be formed by forming a metal material (copper, copper alloy, nickel, nickel alloy, titanium, titanium alloy, silver and silver alloy, etc.) on a polymer material substrate (such as a substrate of polypropylene (PP), polyethylene terephthalate (PET), polybutylene terephthalate (PBT), polystyrene (PS), polyethylene (PE), etc.).
[0087] Optionally, the negative electrode active material may also include negative electrode active materials known in the art for sodium-ion batteries. For example, the negative electrode active material may also include at least one of the following materials: natural graphite, artificial graphite, and mesophase microcarbon spheres (MCMB). These negative electrode active materials may be used alone or in combination of two or more materials.
[0088] Optionally, the negative electrode film layer also includes a conductive agent, which may include at least one of superconducting carbon, acetylene black, carbon black, Ketjen black, carbon dots, carbon nanotubes, graphene, and carbon nanofibers.
[0089] Optionally, the negative electrode film layer further includes an adhesive, which may include at least one of polyvinylidene fluoride (PVDF), polytetrafluoroethylene (PTFE), PVDF-tetrafluoroethylene-propylene terpolymer, PVDF-hexafluoropropylene-tetrafluoroethylene terpolymer, tetrafluoroethylene-hexafluoropropylene copolymer, and fluorinated acrylate resin.
[0090] The above-mentioned negative electrode sheet can be prepared according to conventional methods in the art. For example, the components used to prepare the negative electrode sheet, such as negative electrode active material, conductive agent, binder and any other components, can be dispersed in a solvent to form a negative electrode slurry; the negative electrode slurry is coated on a negative electrode current collector, and after drying, cold pressing and other processes, the negative electrode sheet can be obtained.
[0091] The negative electrode sheet provided in this application includes the negative electrode active material described in the foregoing embodiments. Therefore, when applied to a sodium-ion battery, the negative electrode active material on the surface of the negative electrode sheet can be obtained by disassembling the sodium-ion battery and subjected to XRD analysis to determine its composition, thus enabling the detection of the negative electrode active material described in the foregoing embodiments. Furthermore, after cycling the sodium-ion battery, by disassembling the cycled sodium-ion battery and obtaining the negative electrode active material on the surface of the cycled negative electrode sheet, and performing XRD analysis, compounds formed between the sodium storage material and sodium can be detected. For example, at least one of sodium alloys, sodium oxides, sodium sulfides, sodium selenides, and sodium phosphides.
[0092] [Positive electrode plate]
[0093] The positive electrode includes a positive current collector and a positive electrode film layer disposed on at least one surface of the positive current collector, the positive electrode film layer including a positive electrode active material.
[0094] As an example, the positive current collector has two surfaces opposite each other in its own thickness direction, and the positive electrode film layer can be disposed on either or both of the two opposite surfaces of the positive current collector.
[0095] Optionally, the positive current collector can be a metal foil or a composite current collector. For example, aluminum foil can be used as the metal foil. The composite current collector may include a polymer material substrate and a metal layer formed on at least one surface of the polymer material substrate. The composite current collector can be formed by forming a metal material (aluminum, aluminum alloy, nickel, nickel alloy, titanium, titanium alloy, silver and silver alloy, etc.) on a polymer material substrate (such as a substrate of polypropylene (PP), polyethylene terephthalate (PET), polybutylene terephthalate (PBT), polystyrene (PS), polyethylene (PE), etc.).
[0096] Optionally, the positive electrode active material may include positive electrode active materials known in the art for sodium-ion batteries. As mentioned above, the positive electrode active material may include one or more of polyanionic compounds, transition metal oxides, and Prussian blue compounds. As an example, polyanionic compounds may be compounds having sodium ions, transition metal ions, and tetrahedral anionic units, such as sodium iron phosphate (NaFePO4) and sodium vanadium phosphate (Na3V2(PO4)3). Transition metal oxides may be transition metal oxides having sodium ions, such as sodium copper iron manganate and sodium iron nickel manganate. Prussian blue compounds may be compounds having sodium ions, transition metal ions, and cyanide ions. However, this application is not limited to these materials, and other materials that can be used as positive electrode active materials for sodium-ion batteries may also be used. These positive electrode active materials may be used alone or in combination of two or more materials.
[0097] Optionally, the positive electrode film layer further includes an adhesive, which may include at least one of polyvinylidene fluoride (PVDF), polytetrafluoroethylene (PTFE), PVDF-tetrafluoroethylene-propylene terpolymer, PVDF-hexafluoropropylene-tetrafluoroethylene terpolymer, tetrafluoroethylene-hexafluoropropylene copolymer, and fluorinated acrylate resin.
[0098] Optionally, the positive electrode film layer also includes a conductive agent, which may include at least one of superconducting carbon, acetylene black, carbon black, Ketjen black, carbon dots, carbon nanotubes, graphene, and carbon nanofibers.
[0099] In some embodiments, the positive electrode sheet can be prepared by dispersing the above-mentioned components for preparing the positive electrode sheet, such as positive active material, additives, conductive agents, binders and any other components, in a solvent (e.g., NMP) to form a positive electrode slurry; coating the positive electrode slurry onto a positive current collector, and then obtaining the positive electrode sheet after drying, cold pressing and other processes.
[0100] [Electrolytes]
[0101] The electrolyte acts as a conductor of ions between the positive and negative electrodes. This application does not impose specific restrictions on the type of electrolyte; it can be selected according to requirements. For example, the electrolyte can be liquid, gel, or entirely solid.
[0102] In some embodiments, the electrolyte is an electrolyte solution. The electrolyte solution includes an electrolyte salt and a solvent.
[0103] Optionally, the electrolyte salts include NaPF6, NaBCl4, NaSO3CF3, and Na(CH3)C6H4SO3, etc.
[0104] Optionally, the solvent includes carbonate or ether solvents. Carbonate solvents include cyclic ethylene carbonate (EC), propylene carbonate (PC), fluoroethylene carbonate (FEC), and chain-like dimethyl carbonate (DMC), diethyl carbonate (DEC), methyl ethyl carbonate (EMC), etc.; ether solvents include ethylene glycol dimethyl ether, diethylene glycol dimethyl ether, triethylene glycol dimethyl ether, tetraethylene glycol dimethyl ether, tetrahydrofuran, 1,3-dioxane, etc.
[0105] Optionally, the electrolyte may also include electrolyte additives. For example, electrolyte additives may include negative electrode film-forming additives, positive electrode film-forming additives, and may also include additives that can improve certain battery performance, such as additives that improve battery overcharge performance, additives that improve battery high-temperature or low-temperature performance, etc.
[0106] [Isolation Component]
[0107] In some embodiments, the sodium-ion battery also includes a separator. This application does not impose any particular limitation on the type of separator; for example, the separator can be a separator membrane. The separator membrane can be any known porous structure separator membrane with good chemical and mechanical stability.
[0108] Optionally, the material of the separator can be selected from at least one of glass fiber, non-woven fabric, polyethylene, polypropylene, and polyvinylidene fluoride. The separator can be a single-layer film or a multi-layer composite film, without particular limitation. When the separator is a multi-layer composite film, the materials of each layer can be the same or different, without particular limitation.
[0109] In some embodiments, the above-mentioned positive electrode, negative electrode and separator can be fabricated into an electrode assembly by a winding process or a stacking process.
[0110] In some embodiments, the battery cell may include an outer packaging. This outer packaging can be used to encapsulate the electrode assembly and electrolyte described above.
[0111] In some embodiments, the outer packaging of the battery cell can be a rigid shell, such as a hard plastic shell, an aluminum shell, or a steel shell. The outer packaging of the battery cell can also be a flexible package, such as a pouch. The material of the flexible package can be plastic; examples of plastics include polypropylene, polybutylene terephthalate, and polybutylene succinate.
[0112] Sodium-ion batteries
[0113] This application also provides a sodium-ion battery, which includes the negative electrode sheet in any of the foregoing embodiments.
[0114] This application does not impose any particular limitation on the shape of the sodium-ion battery; it can be cylindrical, square, or any other arbitrary shape. For example, Figure 1This is an example of a sodium-ion battery 100 with a square structure.
[0115] Figure 2 This is a sample sodium-ion battery module 200. (See reference...) Figure 2 In the battery module 200, multiple sodium-ion batteries 100 can be arranged sequentially along the length of the battery module 200. Of course, they can also be arranged in any other manner. Furthermore, the multiple sodium-ion batteries 100 can be secured using fasteners.
[0116] Alternatively, in one embodiment, the battery module 200 may further include a housing with a receiving space in which a plurality of sodium-ion batteries 100 are received.
[0117] Optionally, in one embodiment, the battery module 200 can also be assembled into a battery pack. The number of battery modules 200 contained in the battery pack can be one or more, and the specific number can be selected by those skilled in the art according to the application scenario and capacity of the battery pack.
[0118] Figure 3 and Figure 4 This is a sample battery pack 300. (See reference...) Figure 3 and Figure 4 The battery pack 300 may include a battery box and multiple battery modules 200 disposed within the battery box. The battery box includes an upper box 301 and a lower box 302, with the upper box 301 covering the lower box 302 to form a closed space for accommodating the battery modules 200. The multiple battery modules 200 may be arranged in any manner within the battery box.
[0119] It should be understood that in some embodiments, the battery pack 300 described above is also referred to as a battery. The sodium-ion batteries 100 can be first assembled into battery module 200, and the battery pack 300 is composed of battery module 200. Alternatively, the battery pack 300 can be directly assembled from sodium-ion batteries 100, omitting the intermediate form of battery module 200.
[0120] In addition, this application also provides an electrical device, which includes at least one of the sodium-ion battery 100, battery module 200, or battery pack 300 provided in this application. The sodium-ion battery 100, battery module 200, or battery pack 300 can be used as the power source of the electrical device or as the energy storage unit of the electrical device. The electrical device may include mobile devices (e.g., mobile phones, laptops, etc.), electric vehicles (e.g., pure electric vehicles, hybrid electric vehicles, plug-in hybrid electric vehicles, electric bicycles, electric scooters, electric golf carts, electric trucks, etc.), electric trains, ships and satellites, energy storage systems, etc., but is not limited thereto.
[0121] As an electrical device, the quantity of sodium-ion batteries 100, battery modules 200, or battery packs 300 can be selected according to its usage requirements.
[0122] This is an example of an electrical device. The device is a pure electric vehicle, a hybrid electric vehicle, or a plug-in hybrid electric vehicle, etc. To meet the high power and high energy density requirements of the secondary battery for this device, a battery pack 300 or a battery module 200 can be used.
[0123] Another example device could be a mobile phone, tablet, or laptop. These devices typically require a slim and lightweight design and can use a sodium-ion battery (100) as their power source.
[0124] The following describes embodiments of this application. The embodiments described below are exemplary and are only used to explain this application, and should not be construed as limiting this application. Where specific techniques or conditions are not specified in the embodiments, they are performed according to the techniques or conditions described in the literature in this field or according to the product instructions. Reagents or instruments used, unless otherwise specified, are all conventional products that can be obtained commercially.
[0125] [Examples and Comparative Examples]
[0126] Example 1
[0127] (1) Preparation of positive electrode sheet
[0128] NaFe, the positive electrode active material 0.33 Mn 0.33 Ni 0.33 O2, conductive agent carbon black, and binder polyvinylidene fluoride (PVDF) are mixed thoroughly in an appropriate amount of NMP at a mass ratio of 8:1:1 to form a positive electrode slurry. The positive electrode slurry is coated onto the positive electrode current collector aluminum foil, and after drying and rolling, a positive electrode sheet is obtained.
[0129] (2) Preparation of negative electrode sheet
[0130] The negative electrode active material, conductive agent acetylene black, and binder polyvinylidene fluoride (PVDF) are thoroughly mixed in an appropriate amount of NMP at a mass ratio of 8:1:1 to form a negative electrode slurry. The negative electrode slurry is coated onto the negative electrode current collector copper foil, and the negative electrode sheet is obtained after drying and rolling.
[0131] The negative electrode active materials include hard carbon and a conversion-type sodium storage material. The conversion-type sodium storage material is Sn, with an average volumetric particle size distribution Dv502 = 6 μm, a specific capacity W2 = 720 mAh / g, and a mass content m2 = 2.5% in the negative electrode active materials. The true density of hard carbon ρ = 1.5 g / cm³. 3The mass content of hard carbon in the negative electrode active material is m1 = 97.5%, and the specific capacity of hard carbon is W1 = 315 mAh / g. The measured powder compaction density of the negative electrode active material is α = 1 g / cm³. 3 .
[0132] (3) Assembly of sodium-ion batteries
[0133] The positive electrode, separator, and negative electrode are stacked in sequence, with the separator positioned between the positive and negative electrodes. After stacking, an electrode assembly is formed. The electrode assembly is then placed in a packaging shell, and a 1 mol / L NaPF6 electrolyte is added. After encapsulation, formation, and settling processes, a sodium-ion battery is obtained.
[0134] Example 2
[0135] Compared to Example 1, in Example 2, ρ = 1.5 g / cm³ 3 W1 = 350mAh / g.
[0136] Example 3
[0137] Compared with Example 1, in Example 3, ρ = 2.0 g / cm³ 3 W1 = 280mAh / g.
[0138] Example 4
[0139] Compared to Example 1, in Example 4, m1 = 80% and m2 = 20%.
[0140] Example 5
[0141] Compared to Example 1, in Example 5, m1 = 99% and m2 = 1%.
[0142] Example 6
[0143] Compared to Example 1, in Example 6, m1 = 70% and m2 = 30%.
[0144] Example 7
[0145] Compared with Example 1, in Example 7, the conversion-type sodium storage material is Bi, Dv502 = 5.8 μm, W2 = 550 mAh / g.
[0146] Example 8
[0147] Compared with Example 1, in Example 8, the conversion sodium storage material is Sb, Dv502 = 5.4 μm, W2 = 490 mAh / g.
[0148] Example 9
[0149] Compared with Example 1, in Example 9, the conversion sodium storage material is P, Dv502 = 6.1 μm, W2 = 1500 mAh / g.
[0150] Example 10
[0151] Compared with Example 1, in Example 10, the conversion sodium storage material is SnO2 with Dv502 = 6 μm and W2 = 700 mAh / g.
[0152] Example 11
[0153] Compared with Example 1, in Example 11, Dv502 = 15 μm and W2 = 695 mAh / g.
[0154] Example 12
[0155] Compared with Example 1, in Example 12, Dv502 = 25 μm and W2 = 680 mAh / g.
[0156] Example 13
[0157] Compared with Example 1, in Example 13, the embedded sodium storage material is Si, Dv502 = 6 μm, W2 = 300 mAh / g.
[0158] Comparative Example 1
[0159] Compared to Example 1, Comparative Example 1 used only hard carbon as the negative electrode active material.
[0160] Comparative Example 2
[0161] Compared to Example 1, the true density ρ of the hard carbon in Comparative Example 2 was 2.3 g / cm³. 3 The specific capacity of hard carbon is W1 = 70 mAh / g.
[0162] Table 1 Product parameters of the examples and comparative examples
[0163] In Table 1, “ρ” represents the true density of hard carbon in the negative electrode active material, “m1” represents the mass content of hard carbon in the negative electrode active material, “W1” represents the specific capacity of hard carbon, “convertible sodium storage material” represents the type of convertible sodium storage material in the negative electrode active material, “m2” represents the mass content of convertible sodium storage material in the negative electrode active material, “Dv502” represents the average volumetric particle size of the convertible sodium storage material, and “W2” represents the specific capacity of the convertible sodium storage material.
[0164] The performance test results of the sodium-ion batteries in the above embodiments and comparative examples are detailed in Table 2.
[0165] Table 2. Battery performance test results for different embodiments and comparative examples. Example 1 120 >0.15 Example 2 127 >0.15 Example 3 110 >0.15 Example 4 125 >0.15 Example 5 113 >0.15 Example 6 130 >0.15 Example 7 117 >0.15 Example 8 115 >0.15 Example 9 123 >0.15 Example 10 119 >0.15 Example 11 121 >0.15 Example 12 118 >0.15 Example 13 114 >0.15 Comparative Example 1 109 ≤0.15 Comparative Example 2 60 ≤0.15
[0166] In Table 2, "Battery Energy Density" represents the energy density of each sodium-ion battery in the examples and comparative examples, and "Thermal Spread Rate" represents the thermal spread rate measured when the negative electrode is removed after disassembling the sodium-ion battery and subjected to a thermal spread test.
[0167] Based on the comparative analysis of the examples and comparative examples, it can be seen that in the sodium-ion batteries of Examples 1-13, the negative electrode active material contains materials with a true density of 1.3 g / cm³. 3 -1.8g / cm 3 In contrast, the hard carbon and conversion-type sodium storage materials used in the examples showed thermal runaway rates greater than 0.15 m / s in the thermal runaway test for sodium-ion batteries. However, in Comparative Examples 1-2, the negative electrode active materials lacked conversion-type sodium storage materials capable of reacting with sodium to form sodium compounds, or the true density of the hard carbon was outside a suitable range, resulting in thermal runaway rates less than or equal to 0.15 m / s in the thermal runaway test. Furthermore, the energy densities of the examples were superior to those of the comparative examples. This demonstrates that by combining hard carbon and conversion-type sodium storage materials with suitable true densities, the formation of metalloid sodium during sodium-ion battery cycling can be reduced, effectively lowering the risks of thermal runaway and thermal runaway in sodium-ion batteries, while also enabling sodium-ion batteries to achieve higher energy densities.
[0168] A comparison of data from Examples 1-3 and Comparative Example 2 shows that the higher the true density of hard carbon, the lower its specific capacity. A possible mechanism is that the structure of hard carbon with higher true density is closer to graphite, and graphite has extremely low sodium storage capacity. The closer the structure is to graphite, the weaker the sodium storage capacity of the material, resulting in a lower specific capacity and a smaller contribution to energy density. Therefore, by selecting hard carbon with a true density within a suitable range, the negative electrode active material provided in this application can reduce the risks of thermal runaway and thermal propagation in sodium-ion batteries while also possessing a high energy density.
[0169] A comparison of data from Examples 1 and 4-6 shows that increasing the mass content of the conversion-type sodium storage material in the negative electrode active material helps to improve the energy density of sodium-ion batteries. While simultaneously considering the cycle stability of sodium-ion batteries, controlling the mass content of the conversion-type sodium storage material within a suitable range can reduce the risks of thermal runaway and thermal propagation while simultaneously increasing the energy density of sodium-ion batteries.
[0170] Examples 7-10 and 13 illustrate examples of different types of conversion-type sodium storage materials combined with hard carbon. It can be seen that different types of conversion-type sodium storage materials can reduce the risk of thermal runaway and thermal propagation in sodium-ion batteries and enable sodium-ion batteries to have high energy density.
[0171] Comparing the data from Examples 1 and 11-12, it is evident that the smaller Dv50 of the intercalated sodium storage material results in a higher specific capacity. The possible mechanism is that larger particle sizes require sodium ions to travel a greater distance to intercalate, potentially leading to insufficient sodium storage sites during actual battery cycling. Therefore, smaller particle sizes in the intercalated sodium storage material are more conducive to sodium ion intercalation, resulting in a higher actual sodium ion storage capacity, closer to the theoretical value. Thus, selecting intercalated sodium storage materials with smaller particle sizes can further improve the energy density of sodium-ion batteries.
[0172] Next, the testing methods for the physical parameters and performance parameters involved in the embodiments of this application will be introduced.
[0173] 1. True density test method
[0174] The true density of a material can be tested using methods known in the art. For example, instruments such as the AccuPyc 1340, the Antonpah DMA 4200M, and the ZS-102 tap density meter can be used to test the true density of a material. A specific example of testing true density is given below.
[0175] Sample requirements: Powder (preferably 10mL); Blocks: Sizes less than the following: diameter 15mm, height 35mm, total volume not less than 6mL. True density refers to the actual mass of a solid substance per unit volume in an absolutely dense state, i.e., the density after removing internal pores or voids between particles.
[0176] The material to be tested is placed in a true density analyzer, using helium as the medium. The measuring chamber is gradually pressurized to a fixed value, causing the helium to expand and enter the expansion chamber. The equilibrium pressure of the two processes is automatically recorded by the instrument. Based on the law of conservation of mass, the volumes of the measuring chamber and the expansion chamber are calibrated using a standard sphere, and then the volume of the material is determined to calculate the true density. Applying Archimedes' principle—the gas expansion and displacement method—and utilizing Bohr's law (PV = nRT) for small-molecule inert gases under certain conditions, the true volume of the material to be tested is determined by measuring the reduction in gas volume in the sample testing chamber caused by the insertion of the sample. Thus, its true density is obtained: True density = mass / true volume.
[0177] It should be understood that the above fixed values are manually set based on testing experience and can be adjusted as needed. After pressurizing to this fixed value, further pressurization will result in the volume of helium in the expansion chamber no longer changing or changing only slightly; for example, the volume change rate is less than or equal to 1%.
[0178] 2. Test method for average volumetric particle size
[0179] Dv50 represents the particle size corresponding to a cumulative volume distribution percentage of 50% for the negative electrode active material. In this application, Dv50 has a meaning known in the art and can be determined using instruments and methods known in the art. For example, it can be determined using a laser particle size analyzer (e.g., Master Size 300) according to GB / T 19077-2016 Particle Size Distribution Laser Diffraction Method.
[0180] 3. BET Testing Methods
[0181] The test method refers to the standard GB / T19587-2004 "Determination of specific surface area of solid substances by gas adsorption BET method".
[0182] Take 8g-15g of the sample to be tested and place it into a sample tube, recording the initial mass of the sample. Place the weighed sample into the NOVA2000e testing equipment. Then begin degassing and heat the sample to 200℃, maintaining this temperature for 2 hours. Record the mass of the degassed sample afterward. Then, reload the degassed sample into the equipment and pour in liquid nitrogen for the BET test. Set the nitrogen pressure to 0.08MPa-0.12MPa and the heating temperature to 40℃-350℃. After the test, read the specific surface area from the test results.
[0183] 3. Test method for powder compaction density
[0184] The compacted density of a material powder can be tested using methods known in the art. For example, it can be tested using an electronic pressure testing machine (such as UTM7305) according to GB / T 24533-2009: a certain amount of powder is placed on a special compaction mold, different pressures are set, and the thickness of the powder under different pressures can be read on the equipment, and the compacted density under different pressures can be calculated.
[0185] 4. Method for testing sodium ion energy density
[0186] Mass energy density (Wh / kg) = Battery capacity (mAh) × Voltage plateau 3.0V / Battery weight.
[0187] 5. Test method for heat spread
[0188] The cycled sodium-ion battery is disassembled to obtain the cycled negative electrode sheet. Ignition of this negative electrode sheet allows direct observation of heat spread. More specifically, the prepared cell is charged to 4.0V, disassembled in a glove box, and the negative electrode sheet is removed and cut into strips of 30cm × 15cm. Forced ignition is then performed using a heat gun (200℃) in an inert glove box, and the combustion rate and time are recorded. Thus, heat spread can also be quantified using combustion rate and time. Thermal propagation rate: v = L / (t_P - t_b)
[0189] Where L is the distance between the two sensing lines T-ignition and T-propagation, t_P is the moment when the temperature at the electrode propagation position reaches its maximum, and t_b is the moment when the temperature at the ignition position reaches its maximum.
[0190] Although this application has been described with reference to preferred embodiments, various modifications can be made thereto and components can be replaced with equivalents without departing from the scope of this application. In particular, the technical features mentioned in the various embodiments can be combined in any manner, provided there is no structural conflict. This application is not limited to the specific embodiments disclosed herein, but includes all technical solutions falling within the scope of the claims.
Claims
1. A negative electrode active material, characterized in that, include: Hard carbon, wherein the true density ρ of the hard carbon satisfies: 1.3 g / cm³ 3 ≤ρ≤2.0g / cm 3 ; A convertible sodium storage material, wherein the convertible sodium storage material is capable of forming a compound with sodium; The mass content m2 of the conversion-type sodium storage material in the negative electrode active material satisfies: 1%≤m2≤20%.
2. The negative electrode active material according to claim 1, characterized in that, The mass content m1 of hard carbon in the negative electrode active material satisfies: 80%≤m1≤99%.
3. The negative electrode active material according to claim 1 or 2, characterized in that, The mass content m1 of hard carbon in the negative electrode active material satisfies: 85%≤m1≤98%.
4. The negative electrode active material according to claim 1 or 2, characterized in that, The mass content m2 of the conversion-type sodium storage material in the negative electrode active material satisfies: 2%≤m2≤15%.
5. The negative electrode active material according to claim 1, characterized in that, The conversion-type sodium storage material includes at least one of the following: alloy sodium storage material, metal oxide sodium storage material, metal sulfide sodium storage material, metal selenide sodium storage material, and metal phosphide sodium storage material.
6. The negative electrode active material according to claim 5, characterized in that, The alloy-type sodium storage material includes at least one of Sn, Ge, Pb, P, Sb, Bi, Si, and their alloys.
7. The negative electrode active material according to claim 5 or 6, characterized in that, The metal oxide sodium storage material includes at least one of the following: oxides of Sn, Ge, Pb, Sb, Bi, and Si.
8. The negative electrode active material according to claim 5 or 6, characterized in that, The metal sulfide sodium storage material includes at least one of the following: Sn sulfide, Ge sulfide, Pb sulfide, P sulfide, Sb sulfide, Bi sulfide, and Si sulfide.
9. The negative electrode active material according to claim 5 or 6, characterized in that, The metal selenide sodium storage material includes at least one of the following: Sn selenide, Ge selenide, Pb selenide, P selenide, Sb selenide, Bi selenide, and Si selenide.
10. The negative electrode active material according to claim 5 or 6, characterized in that, The metal phosphide sodium storage material includes at least one of the following: Sn phosphide, Ge phosphide, Pb phosphide, Sb phosphide, Bi phosphide, and Si phosphide.
11. The negative electrode active material according to claim 1, characterized in that, The compounds formed by the conversion-type sodium storage material and sodium include at least one of the following: sodium alloy, sodium oxide, sodium sulfide, sodium selenide, and sodium phosphide.
12. The negative electrode active material according to claim 1, characterized in that, The average volumetric particle size Dv50 of the conversion sodium storage material satisfies: 5 μm ≤ Dv50 ≤ 30 μm.
13. The negative electrode active material according to claim 1, characterized in that, The average volumetric particle size Dv50 of the conversion sodium storage material satisfies: 5 μm ≤ Dv50 ≤ 25 μm.
14. The negative electrode active material according to claim 1, characterized in that, The specific capacity W1 of the hard carbon satisfies: 150 mAh / g ≤ W1 ≤ 350 mAh / g.
15. The negative electrode active material according to claim 1, characterized in that, The specific capacity W1 of the hard carbon satisfies: 280≤W1≤350 mAh / g.
16. The negative electrode active material according to claim 1, characterized in that, The discharge capacity W2 of the conversion sodium storage material satisfies: 300 mAh / g ≤ W2 ≤ 2000 mAh / g.
17. The negative electrode active material according to claim 1, characterized in that, The discharge capacity W2 of the conversion sodium storage material satisfies: 300 mAh / g ≤ W2 ≤ 1500 mAh / g.
18. A negative electrode sheet, characterized in that, The negative electrode sheet comprises the negative electrode active material as described in any one of claims 1-17.
19. A sodium-ion battery, characterized in that, The sodium-ion battery includes the negative electrode as described in claim 18.
20. An electrical appliance, characterized in that, The electrical device includes the sodium-ion battery as described in claim 19.
Citation Information
Patent Citations
Hard carbon materials
US20130252082A1
Nonaqueous electrolyte power storage element
WO2022181516A1